Knowledge, awareness, and attitude among practicing orthodontist on teledentistry during COVID pandemic in Kerala: A cross-sectional survey - Pradeep Philip George; Terry Thomas Edathotty; S Gopikrishnan; P S Prasanth; Sandeep Mathew; A A Mohammed Ameen (Wolters Kluwer Medknow Publications, 2021)
Background: Considering the gravity of coronavirus disease 2019 (COVID-19) and its potential to unfold within the dental workplace or institutions, a shift from traditional dental practice to a newer method is needed. Teledentistry is widely being practiced in this pandemic era for the diagnosis and to give instructions to the patients. Hence, an attempt has been made to explore the knowledge, attitude, and awareness of practicing orthodontists regarding the usage of teledentistry during COVID lockdown, in Kerala. Materials and Methods: A cross-sectional, descriptive study was done on about 150 orthodontic professionals. A pretested, self-organized, close-ended survey was managed through online stages that comprised of 15 questions. The information gathered was assembled in a systematic way and investigated regarding recurrence and Chi-square test was utilized for the examination of frequencies. Results: It was observed that 93.3% orthodontic practitioners had knowledge regarding teledentistry and a positive attitude toward teledentistry was shown by younger age group practitioners and those who were working in institutions (P < 0.05). 77.3% believed that teledentistry can save dentist's time and 71.3% responded that the new technology can be helpful in reducing the cost of treatment for patients. Conclusion: The knowledge, awareness, and attitudes were discovered to be acceptable among the orthodontic practitioners. Younger practitioners had more positive attitude toward teledentistry, and there was an overall positive attitude for using teledentistry as a temporary alternate for direct patient contact in COVID-19 pandemic time.